ASSESSMENT OF FORESTRY MANAGEMENT PRACTICES FOR IMPROVING TIMBER PRODUCTION IN KADUNA STATE, NIGERIA - Chinenyea, Nwankwo Franca; Ogbanjeb, Okwori Robert; Maikc, Mohammed Bala (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The scarcity of high-grade timber, the substitution of low-grade timber for high-grade timber by furniture makers and the inflation on the prices of available timber has caused great concern by the users of timber products. This study was carried out to identify forestry management practices for improving timber production. The area of the study is Kaduna State Nigeria. A survey research design was employed for the study. A total of 102 respondents were used as the study population. A structured questionnaire was developed and used for data collection. The Mean and Standard Deviation were used to answer research questions, while z- test statistic was employed to test the three null hypotheses. The Statistical Package for Social Sciences (SPSS) version 20.00 was employed for all statistical calculations. The findings of the study revealed that Clear cutting, Shelterwood, Seed tree, incorporating Villagers into the protection of forest and forest reserves were the forestry management practices for timber production. It was recommended that more timber plantations should be established to meet the timber demand and also to reduce the logging pressure placed on existing forest reserves, Non-Governmental Organizations (NGOs) with interest in the conservation of natural resources should be incorporated into the preservation and establishment of forest reserves. The numbers of Forestry staff should be increased because the study revealed that there is inadequate staff for the forest reserves.